Les ignames du Passoré. - Tiama, Djakaridia; Bationo/Kando, Pauline; Nanema, Romaric K.; Sawadogo, Nerbewende; Tao, Issoufou; Traore, Ernrst R.; SAWADOGO, Mahamadou; ZOUNDJIHEKPON, JEANNE; Zongo, Jean-didier (My University, 2014)
Journées portes ouvertes de l’Université de Ouagadougou / Ecole doctorale : Sciences et Technologies